O Trianon do MAM ao MASP arquitetura e política em São Paulo (1946-1968) - Pisani, Daniele 1974- (Editora 34, 2019)
When starting a research on the work of architect Alfonso Eduardo Reidy (1909-1964), Daniele Pisani, professor of history and theory of contemporary architecture in Milan and scholar of modern and contemporary Brazilian architecture, wanted to analyze the project that the modernist architect developed in the early 1950's for the MAM in São Paulo. Reidy, although a key figure in in modern Brazilian architectual history is rarely mentioned. Pisani research work "illuminates decisive passages of a history that remained buried for many decades, in which intersect, in a theatrical script, not only figures of high economic power and such as Ciccillo Matarazzo, Assis Chateaubriand, Nelson Rockefeller, Armando de Arruda Pereira, Jânio Quadros, Adhemar de Barros and Faria Lima, but also architects of the utmost importance, such as Affonso Eduardo Reidy, Oscar Niemeyer, Vilanova Artigas, Lina Bo Bardi and many others. With strict attention to documents, the constant use of primary sources and an extremely accurate critical sense, The Trianon of MAM to MASP subverts consecrated interpretations and proves to be a mandatory reference to understand the relations between architecture, politics and culture in São Paulo from the 1940's to the 1960's.ʺ (HKB Translation) --Verso Cover
Keywords: Niemeyer, Oscar -- 1907-2012; Reidy, Affonso Eduardo -- 1909-1964; Bardi, Lina Bo -- 1914-1992; Artigas, João Batista Vilanova -- 1915-1985; Museu de Arte Moderna São Paulo; Geschichte 1940-1970; Museumsbau; Architektur; São Paulo; Architecture / Brazil / São Paulo / History; Reidy, Affonso Eduardo / 1909-1964 / Criticism and interpretation; Museu de Arte de São Paulo Assis Chateaubriand / History; Museu de Arte Moderna do Rio de Janeiro / History; Architects / Brazil / History / 20th century; Architecture and society / Brazil / São Paulo / History / 20th century; Art museum architecture / Brazil / São Paulo / History / 20th century; Architecture, Modern / 20th century; Reidy, Affonso Eduardo / 1909-1964; Museu de Arte de São Paulo Assis Chateaubriand; Museu de Arte Moderna do Rio de Janeiro; Architects; Architecture; Architecture and society; Architecture, Modern; Art museum architecture; Brazil / São Paulo; Brazil; 1900-1999; Criticism, interpretation, etc; History